Kelimpahan Bakteri Nitrifier Rhizosfer Serelia dan Legum di Kalimantan Selatan - Razie, Fakhrur; Ichriani, Gusti Irya; Utami, Aditya Dyah; Romadhan, Panji (Agrosains : Jurnal Penelitian Agronomi, 2025)
Fertilizer application, especially nitrogen (N), can have a negative impact on the soil and environment. This can be minimized by reducing fertilizer use with the utilization of functional microbes, namely nitrifying bacteria Nitrosomonas sp. and Nitrobacter sp. This study aims to examine the abundance of nitrifier bacteria in the rhizosphere of cereals and legumes. The stages of the study include taking isolate sources and isolating the total bacteria of Nitrosomonas sp. and Nitrobacter sp. The method of taking isolate sources in the rhizosphere of cereals and legumes with a depth of 20 cm. The results showed that the abundance of bacteria differed in various isolate sources. The abundance of Nitrosomonas sp. in isolate sources in the rhizosphere of legumes was higher than in the rhizosphere of cereals. The abundance of Nitrobacter sp. in isolate sources in the rhizosphere of cereals was higher than in the rhizosphere of legumes. Dry land has a relatively higher abundance of soil microbes compared to rice fields. The characteristics of the source land of the isolates and the rhizosphere affect the total abundance of Nitrosomonas sp.and Nitrobacter sp. The soil characteristics of the isolates source and the rhizosphere of different plants affected the total abundance of Nitrosomonas sp. and Nitrobacter sp.